Rancang Bangun Sistem Informasi Manajemen Posyandu Berbasis Web pada Puskesmas Kalanganyar - Siti Mahdiah; Dola Irwanto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Kalanganyar Healt Center is an agency engaged in the health sector whose job is to provide services to the posyandu community. The problem in this research is how to manage posyandu data and make reports to be more efficient in terms of time and cost at the Kalanganyar Healt Center, therefore a computerized Posyandu management information system is needed at the Kalanganyar Health Center. This research uses the waterfall method. The waterfall method has several stages, namely needs analysis, design, programming, testing, and maintenance. Based on the conclusions of the results of this study, it is that a web-based information system can facilitate the completion of the work carried out by puskesmas officers and posyandu cadres in the processing, searching and reporting of posyandu activity data easily and quickly.